Heparin and some mechanisms of its administration in experimental acute pancreatitis - Dembiński, Marcin (2007)
The aim of the study was to determine the influence of heparin administration on the development and treatment of acute pancreatitis induced by either primary vascular or not vascular factor. Heparin administration before induction of acute pancreatitis by ischemia/reperfusion inhibited the development of this disease. It was expressed as an improvement of pancreatic histology, decrease in plasma activity of lipase and amylase and reduction in plasma concentration of IL-1β. Also the pancreatitis-evoked drop of pancreatic DNA synthesis and pancreatic blood flow was abolished. These changes were correlated with the prolongation of APTT and the decrease in plasma D-dimmer concentration. Also in caerulein induced model of pancreatitis, heparin administration inhibited the development of pancreatitis decreasing the pancreas injury in histopathological examination, plasma concentration of IL-1β and plasma activity of lipase and amylase. Pancreatic DNA synthesis and pancreatic blood flow were also improved. Acute pancreatitis induced by caerulein prolonged APTT and increased plasma concentration of D-dimmer, what provide an evidence of intravascular coagulation. Heparin administration, before induction of this type of pancreatitis, decreased the D-dimmer concentration but was without any influence on pancreatic expression of cylcooxygenase-1 and cyclooxygenase-2. Obtained results have
Keywords: caerulein; acute pancreatitis; ischaemia/reperfusion; heparin